Thermogravimetric analysis of Mediterranean plant species - a.P. Dimitrakopoulos (Journal of Analytical and Applied Pyrolysis, 2001)
Twelve dominant Mediterranean plant species were subjected to thermogravimetric analysis (TGA) in air medium, in order to study their thermal degradation process and assess their potential combustibility as natural fuels. Statistically signiﬁcant differences were observed among the values of the pyrolytic parameters of the species analyzed. The mean volatilization rate values resulted in meaningful ranking of the species into vegetation types of similar combustibility, as veriﬁed by observations during actual wildﬁres. The use of TGA as a method for assessing the combustibility of individual plant species seems justiﬁed
Keywords: combustibility; lignocellulosic materials; Mediterranean; natural fuels; pyrolysis; thermogravimetric analysis; wildland fires